IDEA „KODYFIKACJI” W KULTURZE PRAWNEJ EUROPEJSKIEGO OŚWIECENIA - Sójka-Zielińska, Katarzyna (Zeszyty Prawnicze, 2016)
Idea of the Codification in the Legal Culture of the European Enlightenment Summary In XVIII century’s Enlightenment the program of the general law reform was expressed by the idea of codification, i.e. a replacement all existing particular sources of law by a complete, all-comprehensive, uniform body of law. The formal legal code should be an ius certum providing legal security of citizens. Language of code should be clear, simple, universally understood. The code should cover all possible practical cases in order to restrict judges and prevent abuse of power. The greats works of the “enlightened” Philosophers: Montesquieu’s De l’esprit des lois, Filangieri’s La scienza della legislazione, Bentham’s Introduction to the principles of Morals and Legislation, pointed out the methods and techniques of the elaboration of a perfect set of laws.